A new species of Cnemaspis (Sauria: Gekkonidae) from Assam, north-eastern India - Das, I.; Sengupta, S. (Wildlife Heritage Trust of Sri Lanka, 2000)
A new species of Cnemaspis (Sauria: Gekkonidae) is reported from the Mayeng Reserve Forest, Kamrup District, Assam, north-eastern India. The species is considered morphologically similar to south Asian species of the genus, rather than to those of south-east Asia, and can be diagnosed from all described congeners using the following combination of characters: snout-vent length 28.0 mm; canthal ridge absent; no ridges of tubercles along mandible or in nape region; supranasals separated by a single scale; nasals in narrow contact with supralabial I. Three postnasals bound nasal; postmentals separated by one scale; chin shields not separated from infralabials by enlarged scales; no decrease in dorsal scale size posterior to thorax; ventral scales increase in size from chin to gular, pectoral and abdominal regions. Scales on dorsum at mid body much smaller than those of ventrum at same level; scales on vertebral region not reduced, lacking a spinous process; no enlarged tubercles on dorsum; spine-like tubercles on flanks; pectoral and abdominal scales smooth, imbricate, not distinctly elongated; no preanal or femoral pores; no preanal groove; no enlarged series of subtibial scales; 2-5 greatly enlarged basal scansors; tail segmented, with enlarged flattened scales forming whorls; ventral surface of tail with a median, continuous series of enlarged scales, supralabials (to mid orbit position) 8-9; infralabials 7; interorbital scale rows (at midpoint of orbit) 5; mid-ventral scale rows to lowest row of tubercles 24-26